Strategy Evaluation of BPJS Patient Service Performance (Case Study at Regional General Hospital dr. R. Soetijono Blora) - Noor, Munawar (Forum Ilmu Sosial, 2021)
The performance strategy of health services was for the community carried out by the government by health service institutions. The hospital was one of the service units, which went about to treat or reduce patient suffering through quality service strategies. The quality of health services for the community was the concern of the community and various independent institutions. Health services were said to be of good quality if they satisfied service users and the procedures for their implementation were in accordance with the code of ethics and standards that have been set. As one of the public service units, the hospital was demanded by both the owner and the community to always increase the quantity and quality of services to the community, especially BPJS patients. Community satisfaction at the hospital would have an impact on trust in the hospital, people would visit and if necessary, they queued up to get hospital services. The problem in this study is: How is the service performance strategy for BPJS patients at the DR. R. Soetijono, Blora. The conclusions of this study as: in general, the performance of RSUD dr. R. Soetijono Blora was classified as good, of the 7 strategic goals there is only 1 (target) which was of less value. Judging from the satisfaction index (Community Satisfaction Survey) RSUD dr.R. Soetijono Blora got a score of 76.57 (in the good category) in 2020. The recommendations from this research were the required intensive steps related to improving services at RSUD dr. R. Soetijono Blora to improve the strategy that was still lacking.